Peritoneal Dialysis and Malignancy: An Experience With a Patient Complicated by Gastric Carcinoma. Issue 12 (March 2019) - Akimoto, Tetsu; Muto, Shigeaki; Kutsuwada, Tatsuya; Kutsuwada, Keiko; Nagata, Daisuke
An 86-year-old man who had been treated with peritoneal dialysis for 14°months due to end-stage kidney disease secondary to hypertensive nephrosclerosis presented with a recent history of malaise, abdominal discomfort, and anorexia. An endoscopic evaluation revealed an elevated, ulcerated, and friable lesion around the lesser curvature of the stomach. The concurrent gastric biopsy specimens revealed moderately differentiated adenocarcinoma, while a cytological examination of the dialysis fluid revealed clusters of malignant cells. This is the first report illustrating a case of a Borrmann type 3 gastric cancer with synchronous peritoneal involvement in which the assessment of the disease state was aided by the cytological analysis of peritoneal effluent. Several concerns relating to this pathology are also discussed.